Representasi Kepemimpinan Dalam Film Barbie - Respati, Arum Indah; Sari, Sapta; Dianthi , Martha Heriniazwi (CV. Era Digital Nusantara, 2024)
Leadership is the power to influence someone to do or not do something. For this reason, leadership requires the active use of abilities to influence others and in realizing the goals of the organization that have been set. Leadership is a behavior of individual who leads the activities of a group to a goal that wants to be created together, so this research aims to find out leadership representation in Barbie movie. The theory used is Roland Barthes Semiotics that known as one of the structural thinkers who are keen to practice Saussure's linguistic and semioligi models. Qualitative research method is a research method used in research natural object conditions, (as opposed to the experiments) where the researcher is the key instrument, data collection techniques are triangulated (combined), data analysis is inductive. The results of this study are connotative analysis in the scene opens up deeper layers of meaning from the narrative, highlighting the psychological, social, and political aspects contained in it. Barbie's tears, as a symbol of sadness, not only reflect her emotional expression, but also connote vulnerability and weakness often related to feminine stereotypes. It shows how gender norms influence the way we interpret and respond to one's emotions, as well as reflecting power dynamics in society. The changes that take place in Barbie's home, from a beautiful and comfortable place to something she no longer recognizes, reflect the consequences of the social changes brought about by patriarchy. Patriarchy, as a symbol of masculine domination, is present in the changes brought by Ken. This highlights how patriarchal ideology affects the personal dynamics between Barbie and Ken, as well as the social and cultural structures in Barbie Land. It provides an example of how gender ideology affects everyday reality.